The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15866/irecos.v10i3.5763
|View full text |Cite
|
Sign up to set email alerts
|

Towards Developing Collaborative Experience Based Factory Model for Software Development Process in Cloud Computing Environment

Abstract: Knowledge and experience are important assets for software organizations. In today's global software development trends, development teams are no longer located in single premise; they are spreading across national and geographic boundaries. As a software project progresses, more and more activities are involved which results with the accumulation of knowledge and experiences. Maintaining and reusing of past experiences are vital; and it is even more crucial for distributed teams. In order to sustain in today'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A method service proposes to capture the software process/ method modular construct in a service-based specification. This in turn would pave the way for new promises in software process knowledge sharing and reuse in the service-oriented architecture [48]. However, the modularization of software process models and its presentation in such approaches is not handled according to concepts, principles and modeling formalism that conform to service-oriented architecture and service-orientation design principles.…”
Section: Ii2 Situational Methods Engineeringmentioning
confidence: 99%
“…A method service proposes to capture the software process/ method modular construct in a service-based specification. This in turn would pave the way for new promises in software process knowledge sharing and reuse in the service-oriented architecture [48]. However, the modularization of software process models and its presentation in such approaches is not handled according to concepts, principles and modeling formalism that conform to service-oriented architecture and service-orientation design principles.…”
Section: Ii2 Situational Methods Engineeringmentioning
confidence: 99%
“…Some examples include ontology-based solution [3], [4], multi-agent-based [11], [12], and semantic web [13], [14]. It is found that the number of EF based approach for SD process are still insignificant [1]. One of the studies that adopted EF concept was the study by Ivarsson and Gorschek [2] who proposed Practice Selection Framework (PSF) to support utilizing postmortems for organizational improvements.…”
Section: A Conceptual Modelmentioning
confidence: 99%
“…The knowledge and experiences gained during development have become important assets in software organizations. In the previous work, via a systematic literature review [1], it has been identified that there are issues in knowledge management for SD, and it is even more challenging for distributed teams. The main challenges identified are inefficient knowledge transfer and information flow [2], [3], misinterpretation, and inconsistencies [4], [5], and additionally, organizations fail to learn [6].…”
Section: Introductionmentioning
confidence: 99%
“…The initial model, EBF-SD as proposed in [1] is then named as SDeX (Software Development eXperience Factory) in this study. For simplicity, 'knowledge and experience' are referred to 'experience' in this paper.…”
Section: Prototype Developmentmentioning
confidence: 99%
“…Aforementioned, an experience based factory model for SD process named as EBF-SD has been proposed in [1]. In this paper, further details on the prototype and architectural design of the model with the integration of automation process with workflow, intelligent agents and cloud computing are discussed.…”
mentioning
confidence: 99%